Modelling of Non-Financial Factors Affecting Yemen Small Medium Enterprises (SMEs) Performance Using AMOS - Mohamed Abdulrazaq, Esmail Hassan; Ahmad, Ahmad Nur Aizat (International Journal of Sustainable Construction Engineering and Technology, 2024)
This study exhibits the construction of a structural relationship model of Non-Financial Factors that include innovation, training, human capital, and market orientation on the performance of Yemen's Small Medium Enterprises (SMEs). The modelling was done using the AMOS-SEM software. Structural Equation Modelling (SEM), route analysis, and confirmatory factor analysis are all performed using the software. It is well-known for its visual approach, which enables users to graphically build models with basic sketching tools and analysts to participate in intricate statistical modelling. The modelling examines the specific effects of these factors and discloses key contributors to the success or failure of SMEs. Data used for modelling was collected from 350 valid responses of employees in the Yemeni manufacturing SME. The findings from the modelling highlight the dominant significance of innovation, as proved by its highest beta coefficient of 0.90, signifying its profound impact on SME performance. Following closely is training, with a coefficient of 0.3, further establishing its crucial role in influencing performance outcomes. Ultimately, this research concludes that the four factors—human capital, innovation, training, and market orientation—exhibit a statistically significant relationship with SME performance within manufacturing sector. The inferences of these findings are of paramount importance to policymakers and practitioners as it offers actionable insights for enhancing SME performance and driving economic growth within Yemen.